Learning by teaching in immersive virtual reality – Absorption tendency increases learning outcomes. (April 2023) - Chiquet, Sandra; Martarelli, Corinna S.; Weibel, David; Mast, Fred W.
Abstract: We investigated the learning outcome of teaching an agent via immersive virtual reality (IVR) in two experiments. In Experiment 1, we compared IVR to a less immersive desktop setting and a control condition (writing a summary). Learning outcomes of participants who had explained the topic to an agent via IVR were better. However, this was only the case for participants who scored high on absorption tendency. In Experiment 2, we investigated whether including social cues in the task instructions enhances learning in participants explaining a topic to an agent. Instruction manipulation affected learning as a function of absorption tendency: Low-absorption participants benefitted most from being instructed to imagine they were helping a student peer pass an upcoming test, while high-absorption participants benefitted more when they were to explain the text to a virtual agent. The findings highlight the crucial role of personality traits in learning by teaching in IVR. Highlights: A learning by teaching paradigm was implemented in immersive virtual reality (IVR). IVR supports learning by teaching in high-absorption individuals. Social cues in the task instruction can compensate for user characteristics. Personal traits should be considered in social IVR.